Palabras escritas al margen de la sociedad - Stanič, Katja (Verba hispanica, 2015)
In this article, based on my thesis entitled A medio camino de un mundo que se eleva, I discuss the role of words in poetry, as understood and interpreted by the Russian formalists and later the Marxists. I focus primarily on the parts of their professional literature which deal with the concept of language and the prospects for the creation of a special poetic language. Based on the writings of Slovenian theorists Rastko Močnik and Miklavž Komelj, I discuss avant-garde art and the political aspects of poetry. The core of the article is an analysis of the selected poems of the Mapuche poet David Aninir Guilitraro; where I discuss his use of words, neologisms and about why and how his poetry is political. I discuss the power of writing, in this case poetry, to (re)create new literary spaces: the domains of encounter, dialogue and culture. In this way, poetry is a political creation. In using words and language, the poet changes them, thus creating new cultural territories. The poet is not acculturated, but he is bi- or multi- cultural; in his poems, he relies on two or more languages, cultures, and thus opens the door to the creation of a new language; not homogeneous and sealed, but heterogeneous and human. This is (should be) at the same time the language of intercultural integration.
Keywords: Aninir Guilitraro, David; mapuška poezija; poezija in politika; bikulturnost; akulturacija; neologizmi